Sheaves of Paragraded Rings - Ilić-Georgijević, Emil; Vuković, Mirjana (Sarajevo journal of mathematics, 2024)
In this paper we deal with sheaves of the category of paragraded rings with the same set of grades $Δ,$ in short, the category of paragraded rings of type $Δ,$ denoted by $R^P_Δ.$ The definition of a sheaf of category $R^P_Δ$ is the same as for any other category, but we are interested in the paragraded structure sheaf, as we named it here, and so, in some way we introduce the theory of paragraded structures into algebraic geometry. For this purpose we need to deal with homogeneous ideals, particularly, we need to introduce the prime spectrum of $R\inobj(R^P_Δ)$ and to analyze the localization of $R$.